NECOP Propagation Experiment: Rain-Rate Distributions Observations and Prediction Model Comparisons - J. S. Ojo; S. E. Falodun (International Journal of Antennas and Propagation)
Empirical distribution functions for one-minute average rain-rate values were compiled for three station year of observations at Nigeria environmental and climatic observatory (NECOP) propagation experiment terminal sites. The empirical distribution functions were compared with cumulative distribution functions generated using four different rain-rate distribution models. It is found that although each of the models shows similar qualitative features at lower exceedance of time, the characteristic at higher time percentages shows quantitative difference from the experimental data except the improved version of Moupfouma model. The results further show that the rainfall rate and the microwave propagation characteristics in this region are out of accord with International Telecommunication Union predictions. This information is vital for predicting rain fading cumulative probability distributions over this region.